Defining web3 : a guide to the new cultural economy - Dylan-Ennis, Paul; Dupont, Quinn; Kavanaugh, Donncha (Emerald Publishing Limited, 2024)
Web3 is the latest transformation of the World Wide Web, centred on public blockchains, Crypto tokens, and an ideology of decentralisation. Defining Web3 presents the state of the art in socio-cultural and economic research from leading scholars in the field of cryptocurrencies and blockchains. Exploring Web3 as a 'crypto-carnival,' the papers in this collection take the carnival as their central motif and organising frame to mirror how Web3 is permeated by the carnivalesque, with its games, play, politics, anarchy, dissimulation, humour, vulgarity, excessive consumption, and counter-cultural aesthetics. Walking the line between both enthusiasts and critics, the authors analyse the token economy's messy complications, excesses, dangers, and tensions, and how they might play out for the future of the Internet. Bringing together researchers, artists, and organisational designers to explore Web3's potential as a progressive platform for creative social coordination, this uniquely experimental volume tackles the deceptively simple question, 'What is Web3?' and imagines where it might take us next.
Keywords: World Wide Web -- Social aspects -- HandBooks, manuals, etc.; Social economy.; Social Science, Technology Studies.; Sociology.; Impact of science and technology on society.; elektronické knihy; electronic books